2011
DOI: 10.2119/molmed.2011.00085
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Potential and Tumor Growth-Inhibiting Effect of Plasma Advanced Glycation End Products in Non-Small Cell Lung Carcinoma

Abstract: The plasma fluorescence related to the standard fluorescence of advanced glycation end products (AGEs) is a simple measurable blood parameter for distinct diseases but its importance in human cancer, including non-small cell lung carcinoma (NSCLC), is unknown. Plasma samples of 70 NSCLC patients who underwent resection surgery of the tumor were analyzed for the distinct AGE-related fluorescence at 370 nm excitation/440 nm emission. In a retrospective study, we tested the prognostic relevance of this AGE-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Moreover, it was shown that AGEs from nutrition also have beneficial effects. For an example, nude mice fed with AGEs from bread crust and increased levels of AGEs in the blood showed a reduced growth of lung cancer in comparison to mice with normal AGE levels (Bartling et al, 2011a). This is in line with data mentioned above that lung cancer patients with high AGErelated fluorescence in plasma have a better postoperative long-term survival.…”
Section: Ages From Nutritionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, it was shown that AGEs from nutrition also have beneficial effects. For an example, nude mice fed with AGEs from bread crust and increased levels of AGEs in the blood showed a reduced growth of lung cancer in comparison to mice with normal AGE levels (Bartling et al, 2011a). This is in line with data mentioned above that lung cancer patients with high AGErelated fluorescence in plasma have a better postoperative long-term survival.…”
Section: Ages From Nutritionsupporting
confidence: 88%
“…Nonsmall cell lung carcinoma patients with high AGE-related plasma fluorescence have a later reoccurrence of the tumor after curative surgery and a higher survival rate compared with patients with low AGErelated plasma fluorescence. In an animal mouse model of the same study, an AGE rich diet was able to reduce the development of tumors (Bartling et al, 2011a). In line with these results, it could be shown that lung cancer patients with diabetes may have some advantages in the survival after tumor resection within the first one-to two years (Bartling et al, 2011b).…”
Section: Lung Cancersupporting
confidence: 54%
“…Notably, glyceraldehyde-derived AGE has been shown to significantly inhibit proliferation of A549 lung cancer cells, but it enhances the migrated and invasive activities of these cells [60]. In terms of lung tumor growth, these findings are partially in accordance with the clinical outcomes [49].…”
Section: In Vitro Studymentioning
confidence: 76%
“…Systematic reviews indicate that a high-AGE diet that often recognized as a Western-style diet containing high-fat/high-sugar foods, refined grains, and red meat [25] or an unhealthy/sedentary lifestyle may increase the body's AGE pool, thereby increasing the risk of cancers such as prostate and pancreatic cancer [25][26][27][42][43][44]. In addition, a series of epidemiological studies have elucidated the association of biological AGE levels with the risk of cancer in smokers [45][46][47][48] and cancer patients [49][50][51]. Studies in Finnish male smokers found that serum CML levels were not associated with the risk of pancreatic or colorectal cancer and were inversely associated with the risk of liver cancer [45][46][47].…”
Section: Epidemiological and Animal Studymentioning
confidence: 99%
“…Dicarbonyl intermediates such as methyl glyoxal cause a lot of structural damage compared to reducing sugars such as glucose. The rate of AGE formation depends on the rate of the formation of highly reactive intermediates due to defective glycolysis pathway and consumption of high sugar diet (Bartling et al 2011;Simm et al 2014). The change in AGE fluorescence with decrease in tryptophan fluorescence can be observed in Fig.…”
Section: Resultsmentioning
confidence: 99%